Making physical examination in medicine user-friendly - Rahman, M.M.; Thomas, Puthiaparampil T. (Malaysian Medical Association, 2022)
Physical examination (PE) techniques used in medical schools appear redundant in several aspects: unnecessarily regimental, lacking in efficiency, and lengthy. Many techniques are sustained solely because of the age-old tradition. This commentary suggests a simplification of PE techniques to make them acceptable to all the stakeholders, such as patients, medical students, and medical teachers. This is especially relevant in this era when imaging is widely used for diagnosis, and the confidence and reliance on PE are declining. Opinions of 10 senior consultants active in medical practice, teaching, and assessment were sought to know their concurrence with the authors’ views. Seven of them provided their opinions, which showed considerable agreement with the authors’ views regarding PE. All the items presented in this paper are mostly supported by the opinions of the senior consultants, textbooks, and literature. We consider sharing this work with the fraternity worthwhile.